Evaluation of social and economic efficiency from the intoduction of acidophilic-whey enriched ice cream - Mykhalevych, Artur; Osmak (Fedchenko), Tetiana; Polishchuk, Galyna; Bandura (Kuzmyk), Uliana (My University, 2021)
Ice cream belongs to the group of dairy desserts that are in great demand among consumers and have a high nutritional value. The modern range of ice cream is quite wide, but unfortunately, almost does not include ice cream with a balanced content of essential nutrients. Instead, the range of domestic ice cream is mainly high-fat products of cream and ice cream groups, although the world's demand for low-calorie milk ice cream is growing every year. To improve the nutritional status of the population of Ukraine, a new type of acidophilic enriched ice cream has been developed at the Department of Milk and Dairy Products Technology of NUFT. Ice cream was produced on the basis of whey with the use of a complex of proteins (whey protein concentrate, sodium caseinate, soy protein isolate) and probiotic starter based on Lactobacillus acidophilus. To improve consumer characteristics, vegetable pectin-containing paste was introduced into fermented milk ice cream.
Keywords: acidophilic-whey ice cream; protein concentrates; pectin-containing puree; кафедра технології молока і молочних продуктів; enriched ice cream; Lactobacillus acidophilus; low-calorie